Sustainable and Earthquake Resistant Structural Systems - Coşkun, Erdal; Kıymaz, Güven; SEÇKİN, EDİP (Crc Press-Taylor & Francis Group, 6000 Broken Sound Parkway Nw, Ste 300, Boca Raton, Fl 33487-2742 Usa, 2010)
Sustainable design, which is one of the most important considerations in any structural design project nowadays, implies many factors such as environmental friendliness, energy competence, functionality, adaptability and efficient use of world's resources. Sustainable design is not only the realization of an architect's vision, but also the notion of the structural engineering regulation. As a result of close cooperation between architects and structural engineers, many brilliant and elegant structures have been built all over the world in the years. On the other hand, with the increasing concern over the environment the architects and structural engineers find themselves once again faced with new challenges. For example, if a structure is not well designed to survive extremely devastating earthquakes, in the economical life of the structure, it will either need to be strengthened or demolished to be rebuilt. Considering the new material which will be consumed for these operations, the environmental effects will be high from the view point of sustainable construction. With this respect, earthquake disaster reduction and sustainable development have equally supportive goals. Technological developments to support earthquake resistant design such as seismic isolations, dampers, durable and flexible structural systems are practical solutions to mitigate the risks against earthquake hazards. If properly designed they may lead to structures that are more efficient in materials and also potentially earthquake resistant without the need for either straightening or demolishing for rebuilding. The leadership of structural engineers adopting new conceptions of functional and structural design and the related innovative techniques for use in sustainable design and minimizing the environmental impact of structures located in seismic areas will be the main focus of this paper. Also, this paper intends to open the discussion among engineers and architects towards a more active contribution to the use of innovative technology for seismic resistant structure within the context for sustainable construction.